The Restrictions for ARTs Applicants in the Light of Human Rights Principles: The Restrictions for ARTs Applicants - Ghadiri , Mahrou (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Having one’s child is one of the strong desires in human beings especially in married persons who sometimes and for some reason are not capable to achieve. Using ARTs is one of their choices to have a baby while there are some barriers and restrictions for the ARTs applicants, both married and singles, to access which may evaluate in different ways, especially in the light of some basic principles of human rights, including the principles of freedom and non-discrimination and along with, because of the vital importance of respect to child’s rights, the principle of the best interest of a child also is a good criterion for this evaluation. Materials and Methods: In the present study, keywords of persons with disabilities, the best interest of the child, principle of freedom, and non-discrimination in databases PubMed, Magiran, SID, ISC, and Google Scholar were searched and relevant literature was searched and analyzed. Ethical Considerations: Honesty in the literature and citation analysis and reporting were considered. Findings: This paper examines the limitations and prohibitions imposed for access to these technologies based on human rights principles. While the respect to freedom and equality of people demands to minimize this restriction, the best interest of a child principle should be the paramount consideration. In the other words, it is necessary to create a balance between the rights of applicants and the rights of the future child with a focus on the best interests of the child and to the main purpose of the application of these techniques for humans, with an approach, preventing dehumanization of the technologies. Accordingly, they recommend the adoption of legislation and regulations, as well as providing specialized counseling services to the applicants and help them during the decision-making by explaining all existing concerns regarding their child’s rights in the future and create a balance between their rights and the future child’s. Conclusion: Access to infertility treatment technologies for infertile couples has always created concerns for service providers about the balance between the rights of parents and future children and policymakers at the macro level. Adoption of laws and regulations, as well as providing specialized counseling services to the applicants and help them during the decision-making by explaining all existing concerns regarding their children’s rights in the future could play an important role in creating a balance between their rights and future child’s. *Corresponding Author: Mahrou Ghadiri; Email: m_ghadiri@sbu.ac.ir; ORCID: https://orcid.org/0000-0001-6756-2188